2008
DOI: 10.1001/archneur.65.7.877
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Predictors in Glioblastoma

Abstract: ecent therapeutic advances have improved standard treatment for patients with newly diagnosed glioblastoma. Unfortunately, even with these improvements, only a fraction of patients derive significant benefit and experience prolonged survival. These findings are consistent with long-standing clinical and recent molecular evidence that subtypes of glioblastoma exist with differing survival rates and response to treatment. However, patients with newly diagnosed glioblastoma are currently treated in a uniform fash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…32 CD15 was also convincingly shown in numerous GSCs to be a tumor-initiating marker 33 and other studies have shown a wide variety of markers (such as L1CAM, 11 and integrin a6…”
Section: Gsc Subtype-specific Markers In Tumorsmentioning
confidence: 82%
See 3 more Smart Citations
“…32 CD15 was also convincingly shown in numerous GSCs to be a tumor-initiating marker 33 and other studies have shown a wide variety of markers (such as L1CAM, 11 and integrin a6…”
Section: Gsc Subtype-specific Markers In Tumorsmentioning
confidence: 82%
“…15 Similarly, a set of genes has been shown to reliably predict the outcome of GBM patients and can potentially guide patients to investigate alternative, more exploratory therapeutic options for tumors that are refractory to current therapies. 11 Bhat et al 5 presented experimental data showing that the conventional antibiotic agent, minocycline, may represent one such candidate treatment for patients with GBM with the MES signature. This agent is clinically attractive because it is already approved by the FDA and has well-known pharmacokinetics and toxicity profiles, 27 is off patent (which would minimize costs), and is known to cross the blood-brain barrier.…”
Section: Clinical Significancementioning
confidence: 99%
See 2 more Smart Citations
“…This seems to be of particular importance in GBM, as these tumors have evolved alternating mechanisms of treatment resistance so that a monotherapy might not target the whole tumor cell population (Cavaliere et al, 2007). To design new, successful strategies, a precise knowledge of tumor-specific alterations is needed, and one promising target for such an approach in GBM is the PI3K/Akt pathway (Colman and Aldape, 2008;Maira et al, 2008).…”
Section: Introductionmentioning
confidence: 99%